Pengaruh Penjualan Bersih, Biaya Produksi, Hutang dan Modal Kerja Terhadap Laba Bersih pada Perusahaan Sektor Industri dan Kimia Periode 2017-2019 - Erlina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Universal, 2022)
Net sales, net profit, debt and working capital are of course very important in a company because they can effect the company’s net profit. This research aims to determine how the effect of Net Sales, Production Costs, debt and Working Capital on Net Profits in basic and chemical industrial sector companies for the period 2017-2019. The sample of this research is industrial companies and chemicals, there were 22 companies selected as samples in this study, the selection is made using purposive sampling method. This type of research is quantitative with secondary data. The data analysis technique is multiple linear regression analysis. Using Microsoft Excel software media and SPSS (Statistical Product and Service Solution) Version 22. results of this study indicate that Net Sales have no significant effect on Net profit, Production Costs have a significant effect on Net profit,debt has a significant effect on Net Profit and Working capital has no significant effect on net profit. In this study, the results of the coefficient of determination or R Square (R2) of 0.436 or 43.6%. Where this means that Net Profit is influenced by Net Sales, Production Costs, debt and Working Capital is not systematically 43.6% and the remaining 56.4% is influenced by other factors.